Pembelajaran IPA Berbasis Problem Based Learning Untuk Meningkatkan Sikap Ilmiah Siswa di SMP Negeri 3 Halmahera selatan - Syamila Umar; Ade Haerullah; Dharmawaty M. Taher (Peneliti.net, 2022)
Science learning in the 2013 revised edition of the 2016 curriculum was developed in an integrated manner in the fields of biology, physics, and chemistry. These three areas are combined in a learning theme. One of the themes of science learning in junior high schools that is adapted to the needs of the development of scientific attitudes is the theme of Environment and Classification. The purpose of this study was to determine the increase in students' scientific attitudes at SMPN 3 South Halmahera after being taught using PBL-based science learning. This research is a quasi-experimental research (Quasy Experiment). The sample of this study consisted of two classes, namely class VII-1 as the experimental class, VII-2 as the control class with a total of 53 students. The instrument used is a questionnaire to measure students' scientific attitude. Data analysis uses the SPSS-assisted normality and homogeneity test, while the hypothesis test uses the Anacova test. The results showed that learning science based on PBL could increase students' scientific attitude by 72.90% with a significant level of 0.001 <0.05.